Ki Hajar Dewantara : Pemikiran dalam Filsafat Kewarganegaraan dan Pendidikan Kewarganegaraan - Zulkifli Alamsah Sutanto (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Ki Hajar Dewantara is a figure in the world of education who is influential in Indonesia and made the date of his birth, namely May 2, a national education day and the father of education is Ki Hajar Dewantara. In his writings he indicated that with various kinds and ways of expressing ideas in accordance with the time and era and the objects he faced, all of Ki Hajar Dewantara's writings contained enthusiasm and breathed struggle. Thoughts about education have also been used until now, including in this case the existence of an independent campus or independent learning initiated by Nadiem Makarim. The purpose of this study was to find out Ki Hajar Dewantara's thoughts on citizenship education. This study uses a literature review study with the existence of data collection techniques using various books and sources in studying it. While the data analysis uses the critical appraisal method. So from this, researchers produce research on civics education based on structure, curriculum content, teachers and learning models in countries that have met education standards in the world, especially in civics education. The results of the study confirm that in Ki Hajar Dewantara's book there is an important point, namely when it is related to the flow in educational philosophy, namely liberalism that regarding tolerance, in Ki Hajar Dewantara's book can be found in education and teaching that is closely related to a particular stream of life, for example religion, belief Spirituality and others in public schools may only be given as "general knowledge" and in the basic principles which presumably can promote the development of character in general, so as a general ethnic, namely manners and decency.